The waste heat of a biofuel-powered SOFC for green hydrogen production using thermochemical cycle; Economic, environmental analysis, and tri-criteria optimization. (1st March 2023) - Alnaqi, Abdulwahab A.; Alsarraf, Jalal; Al-Rashed, Abdullah A.A.A.
Highlights: Biofuel-fired SOFC integrated with thermochemical water splitting for power/hydrogen cogeneration. Tri-criteria optimization based on economic, efficiency and CO2 emission index. Syngas is found to be better than biogas for higher hydrogen production. Biogas is found to be better than syngas for higher power production. Abstract: Biofuels are becoming more and more attractive recently due to their environmental benefits and various applications. In transport section and automotive industries, the biofuels and hydrogen energy are considered promising alternatives for decarburization. In the present research, two biofuel-driven systems for cogeneration of hydrogen and electricity, are suggested and investigated, in which biomass digestion or biomass gasification are compared to provide the required biofuel. The suggested schemes are comprised of SOFC units and thermochemical water splitting cycles, fueled with either biogas or syngas. To comprehensively compare the two schemes, thermoeconomic investigations are established to assess thermodynamic efficiencies as well as produced electricity and hydrogen costs. To examine adverse impacts on the environment, the greenhouse gas emission index is also considered. A sensitivity appraisal is presented for studying the influence of vital design/operation factors on systems' responses and performances. Finally, triple-objective optimization is implemented to detect the best practical operation of the systems for achieving maximum efficiency and minimum emission and product costs. The obtained results under the optimum operation of the systems revealed an interesting feature. It is concluded that each of the two examined systems might be preferred to the other one regarding the desired objective. For instance, if higher hydrogen production (with lower prices) is favored over electricity production, then the gasification-derived scheme is chosen; however, the digestion-based scheme must be selected to gain more electricity.